Designated Income Accounts in Budgetary Units of Municipalities as a Form of Partially Decentralised Redistribution of Public Finance Resources Allocated to Educational Services in Poland - Ofiarski, Zbigniew (Public Governance, Administration and Finances Law Review, 2018)
The Act of 27 August 2009 on public finance, which has been in effect in Poland since the beginning of 2010, has changed the rules regarding the keeping of designated income accounts by a commune’s budgetary units. The Act limited the possibility to create designated income accounts within a commune budgetary units. The right to create such accounts is restricted only to budgetary units which perform educational tasks and is an exception from the principle of full budgeting, a principle meaning that a commune’s budgetary units have to transfer all their income to the commune’s budget, and all expenses of budgetary units are covered from the commune’s budgets. In case of educational services, these public tasks are performed by the commune’s budgetary units as organizational units that are most closely linked with the commune’s budget. An exception here, which is an option at the discretion of the Commune’s Council, is to create a designated income account within the commune’s budgetary unit. The aim of the paper is to analyse and evaluate relevant legislation, judicial practice of courts and regional accounting chambers, as well as the doctrine of administrative law, in particular, educational law and public finance law regarding the scope of applicability of designated income accounts for a commune’s budgetary units that perform educational tasks. The hypothesis that the financing of such expenses through a designated income account is a special form of redistribution of public financial resources in a commune was proven correct. The implementation of this form of funding is justified by the nature of public educational services and allows for more efficient management of this part of public finance. The leading method applied in the paper was the dogmatic and legal method, supported by the empirical and analytical method (in particular with regard to the judicial practice of courts and regional accounting chambers).